Government's Strategy For The Protection Of Musical Copyrights In Digital Transformation Era In Indonesia - Selvira, Rizka; Izzatusholekha, Izzatusholekha (Green Publisher Indonesia, 2023)
The digital transformation era has become a trigger for system changes in government, organizations, the work industry, and also the music industry. Protection of music copyrights has become very popular with the ongoing rampant piracy amid digitalization. The government as a regulator plays a role as an active actor in protecting music copyrighted works. This study aims to analyze the role and strategy of the government in addressing the constraints in maintaining copyrighted music. This study uses the approach of the concept of Intellectual Property Rights and Economic Rights. The result achieved is that the government does not merely try to get rid of music pirates to protect music copyrights in the digital era. Rather, it is by integrating government policies into foreign music platforms to monitor and intervene in piracy. Governments can also create music platforms, and regulate so that pirates are obligated by the terms of those platforms to give credit to the original creators.